2013
DOI: 10.1111/ane.12180
|View full text |Cite
|
Sign up to set email alerts
|

CRP gene polymorphism predicts post-stroke functional outcome in Han Chinese

Abstract: Our study indicates that SNP rs1130864 in the CRP gene is an independent predictor of 3-month functional outcome in patients with first-onset IS in a Han Chinese population. Further studies in different ethnic groups are needed to validate our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Many investigators have demonstrated that a high CRP level after ischemic stroke is a predictive factor of poor outcome [ 7 , 24 , 25 , 26 , 27 , 36 ]. Therefore, testing the CRP level would not only identify patients being at high risk, but would also provide an opportunity for intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many investigators have demonstrated that a high CRP level after ischemic stroke is a predictive factor of poor outcome [ 7 , 24 , 25 , 26 , 27 , 36 ]. Therefore, testing the CRP level would not only identify patients being at high risk, but would also provide an opportunity for intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, an increased level of CRP remarkably associated with the functional prognosis of AIS was observed in multiple studies [ 4 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Nevertheless, most of the previous studies investigating the prognosis of patients with acute ischemic stroke were mainly focused on new stroke attack and mortality [ 21 , 23 , 24 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Serum CRP levels are affected by CRP gene polymorphism (9,42). A previous study found that the CRP gene SNP rs1130864 was an independent predictor of poor short-term prognosis in patients with first ischemic stroke (43). Third, the sampling time following stroke onset may have influenced our results.…”
Section: Discussionmentioning
confidence: 83%
“…Interestingly, six other loci associated with CRP levels in that study were involved in metabolic regulation of diabetes mellitus. It has been also showed that some CRP variants are associated with raised levels of serum CRP while others with decreased ones (Guo et al 2014 ; Kong et al 2012 ; Miller et al 2005 ; Ottaviani et al 2011 ; Russell et al 2004 ).…”
Section: Introductionmentioning
confidence: 99%